A novel glucosamine-linked fluorescent chemosensor for the detection of pyrophosphate in an aqueous medium and live cells. (24th January 2018) - Meng, Qingtao; Wang, Yue; Feng, Huan; Zhou, Fang; Zhou, Bo; Wang, Cuiping; Zhang, Run; Zhang, Zhiqiang
Abstract : A glucosamine-linked Cu 2+ ensemble has been successfully developed for detection of pyrophosphate (PPi) in aqueous medium and in live MD-AMB-231 cells. Abstract : There is growing interest in monitoring the level of pyrophosphate (PPi) in biological processes due to its significant roles in live organisms. In this paper, we described a Cu 2+ ensemble based chemosensor (GN -Cu 2+ ) for highly selective detection of PPi in an aqueous medium and live cells. The fluorescence silent ensemble, GN -Cu 2+, was facilely prepared by complexing of the glucosamine-1, 8-naphthalimide fluorescent ligand (GN ) with paramagnetic Cu 2+ . The structure ofGN was confirmed using 1 H NMR, 13 C NMR and high-resolution mass spectroscopy (HRMS) assays. The spectroscopic characteristics ofGN -Cu 2+ were verified in detail through fluorescence emission and UV-vis spectra titration. The decomplexation ofGN -Cu 2+ by PPi led to the liberation of the fluorescent ligand, GN, and thus the fluorescence was switched on. Spectroscopic studies revealed thatGN -Cu 2+ possesses excellent tolerance to various anions and even other phosphate series, such as AMP, ADP, ATP, and inorganic phosphate (Pi). The detection limit for PPi was calculated to be 1.0 μM.GN -Cu 2+ features several advantages, such as high selectivity, reliability at physiological pH and low cytotoxicity. Intracellular fluorescence imaging measurements indicated thatGN -Cu 2+ is cell membrane permeable and has been successfully used for the detection of PPi in live MD-AMB-231 cells.